Coupled electrical and mechanical processes in polyethylene insulation with water tree having branches of complex structure - Kucheriava, I.M. (Технічна електродинаміка, 2016)
The distributions of electric field, electric force and mechanical stress in the polyethylene insulation of power cable that
contains separate branch of a water tree are studied by computer modeling. Two models of water tree branch which
include a string of water-filled spherical microcavities connected by cylindrical channels with equal radius and with
radius decreasing along the length of the branch are examined. It is shown that the action of electric force and electromechanical
stresses at the ends of thinner tree channels can cause their destruction and then growth of water trees in
polyethylene insulation. Шляхом комп'ютерного моделювання досліджено розподіл електричного поля, електричної сили та механічних напружень
у поліетиленовій ізоляції силового кабеля, яка містить окрему гілку водного триїнга. Розглянуто дві моделі гілки триїнга,
що складається з низки сферичних мікровключень, з'єднаних циліндричними каналами однакового радіуса та каналами, що
зменшуються за товщиною. Показано, що дія електричної сили та розподіл електромеханічних напружень на кінцях більш
тонких каналів триїнга сприяє їхньому руйнуванню і тим самим розвитку триїнгових структур у поліетиленовій ізоляції. Путем компьютерного моделирования исследованы распределения электрического поля, электрической силы и механических
напряжений в полиэтиленовой изоляции силового кабеля, содержащей отдельную ветвь водного триинга. Рассмотрены
две модели ветви триинга, состоящей из цепóчки сферических микровключений, которые соединены цилиндрическими
каналами одинакового радиуса и каналами, уменьшающимися по толщине. Показано, что действие электрической силы и
распределение электромеханических напряжений на концах более тонких каналов триинга способствует их разрушению и
тем самым развитию триинговых структур в полиэтиленовой изоляции.